2015
DOI: 10.1167/iovs.15-17449
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Fractals Correlate With Early Neurodegeneration in Patients With Type 2 Diabetes Mellitus

Abstract: PURPOSE. To investigate the correlation between the retinal vascular fractal dimension (Fd) and neurodegenerative changes in patients with no or mild diabetic retinopathy (DR). METHODS.In this cross-sectional study we examined 103 patients with type 2 diabetes mellitus (T2DM) with no or mild DR. In a randomly selected eye of each patient, Fd was calculated using SIVA-Fractal, a specialized semiautomatic software. Retinal neurodegeneration was evaluated by Topcon 3D OCT-2000 spectral-domain optical coherence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
1
8
1
Order By: Relevance
“…We found only a weak correlation (r ¼ 0.262~0 .289) between the GCC and the SRCL in the two diabetic groups. This was consistent with the findings of Frydkjaer-Olsen et al 38 who also have found a weak correlation (r ¼ 0.20) between the GCL thickness and the retinal fractal dimension of color fundus photographs in patients with no or minimal DR. In addition, they also report an independent association of retinal vessel caliber with the neuroretinal changes in patients with no or early DR. 39 Even though we found a small correlation of the inner retinal layer thickness and the fractal dimension of the SRCL, this did not clearly eliminate the doubt of whether or not the retinal neurodegeneration developed independently or was affected by the damaged retinal vasculature.…”
Section: Discussionsupporting
confidence: 92%
“…We found only a weak correlation (r ¼ 0.262~0 .289) between the GCC and the SRCL in the two diabetic groups. This was consistent with the findings of Frydkjaer-Olsen et al 38 who also have found a weak correlation (r ¼ 0.20) between the GCL thickness and the retinal fractal dimension of color fundus photographs in patients with no or minimal DR. In addition, they also report an independent association of retinal vessel caliber with the neuroretinal changes in patients with no or early DR. 39 Even though we found a small correlation of the inner retinal layer thickness and the fractal dimension of the SRCL, this did not clearly eliminate the doubt of whether or not the retinal neurodegeneration developed independently or was affected by the damaged retinal vasculature.…”
Section: Discussionsupporting
confidence: 92%
“…This was originally postulated by Murray in 1926, 37 and has later been validated for the retinal tree. 38,39 Given that the retinal vascular fractals are associated with subclinical structural changes in early diabetic retinopathy 8 and also predicts long-term microvascular complications, 13 it seems plausible that subtle changes in the retinal vascular system may be an early indicator of upcoming disease.…”
Section: Discussionmentioning
confidence: 99%
“…The retinal fractal dimension has a high intereye agreement in healthy subjects, 4 and even though it generally decreases with aging 4 it is fairly resistant to metabolic changes as measured by different levels of diabetic retinopathy. 5 Studies have demonstrated that the retinal vascular fractals are linked to ocular and systemic diseases like diabetic retinopathy, [6][7][8] stroke, 9,10 and Alzheimer's disease. 11 For instance, the retinal vascular fractal dimension not only correlates to, but also predicts long-term proliferative diabetic retinopathy and other microvascular complications in type 1 diabetes.…”
mentioning
confidence: 99%
“…The research of Frydkjaer-Oslen et al has shown the relationship between early vascular changes and neurogenic changes in patients with type 2 diabetes. 15 They considered retinal fractal analysis an effective method for early identification of neurodegenerative disorders. 15 Fractal analysis is also used in studies of macular vessels.…”
Section: Use In Ophthalmologymentioning
confidence: 99%
“…15 They considered retinal fractal analysis an effective method for early identification of neurodegenerative disorders. 15 Fractal analysis is also used in studies of macular vessels. It allows for reliable, accurate analysis of the structure of the retina in macular degenerations -diabetic maculopathy.…”
Section: Use In Ophthalmologymentioning
confidence: 99%